Graphics shaders : theory and practice - Bailey, Mike; Cunningham, Steve (CRC Press, 2012)
"This book uses examples in OpenGL and the OpenGL Shading Language to present the theory and application of shader programming. It explains how to program graphics shaders effectively for use in art, animation, gaming, and visualization. Along with improved graphics and new examples and exercises, this edition includes a discussion on handling OpenGL's evolution beyond its original built-in functionality, including four new appendices that provide C++ class code to help in this transition. It includes a new chapter on tessellation shaders. It also discusses shaders in multipass rendering and presents new applications including terrain bump mapping, morphing 3D geometry, and wavy glass."